Assembly language programming : ARM Cortex-M3 - Mahout, Vincent (ISTE Ltd. and John Wiley & Sons, 2012)
ARM designs the cores of microcontrollers which equip most "embedded systems" based on 32-bit processors. Cortex M3 is one of these designs, recently developed by ARM with microcontroller applications in mind